Torsades De Pointes Electrical Storm Induced by H1N1 in a Patient with KCNH2 Variant of Unknown Significance - Bashar Khiatah; Jonathan Dukes; Christina Desai; Amanda Frugoli (Case Reports in Cardiology)
This report describes a case of an electrical storm of Torsades De Pointes in a structurally normal heart, following an H1N1 infection in the presence of a genetic variant of unknown significance. The patient was successfully treated with isoproterenol. This case highlights the dilemma of evaluating novel genetic testing results in a clinical setting.